ASSESSMENT OF TREND AND EFFECT OF CLIMATE CHANGE ON OUTPUT OF PALM OIL IN NIGERIA (1975–2018) - NO, ARUOCHA; GC, NNAMERENWA (Innovare Journal of Agricultural Sciences, 2022)
The broad objective of this study was to analyze the impact of climatic change on palm oil output in Nigeria (1975–2018) and identify the trend and factors that influenced output performance of palm oil. The study covered 1975–2018 periods. Secondary data were used for the study. The data were analyzed by the use of econometric methods. Findings showed that climatic parameters of rainfall, temperature, radiation, relative humidity, and sunshine exhibited significant positive trends during the 1975–2018 periods; while palm oil output exhibited a significant negative trend during the 1975–2018 periods. Palm oil output had a compound rate of growth of −1.67% per annum; while the climatic parameters of temperature, rainfall, radiation, sunshine, and relative humidity had a compound rate of growth of 0.1%, 0.7%, 0.9%, 1.5%, and 0.8% per annum, respectively. Palm oil output decelerated in growth; rainfall, sunshine, radiation, and relative humidity accelerated in growth; while, temperature stagnated in growth during the period under study. There were no significant differences in the average rate of growth of palm oil and each pair of the selected climatic parameters considered. In the long run, palm oil output was influenced by current values of area harvested of palm oil, rainfall, temperature, sunshine, and time variable; while, in the short run, palm oil output was influenced by 1 year lag values of area harvested of oil palm, palm oil output, rainfall, sunshine, and temperature based on the specified model. There was a fast adjustment to long run equilibrium among the short run independent variables that estimated the response of palm oil output to climatic change. The conclusion of this study is that climatic change affected the production of palm oil in Nigeria within the periods under study. It is, therefore, recommended that farmers should be educated by government and other stake holders in Nigerian agriculture on possible strategies for mitigating the impact of climate change on cash crop production as well as supported financially to cope with the impact of climatic change.